Growth and Characterization of Core-Shell Structures Consisting of GaN Nanowire Core and GaInN/GaN Multi-Quantum Shell. (29th October 2019) - Kamiyama, Satoshi; Lu, Weifang; Takeuchi, Tetsuya; Iwaya, Motoaki; Akasaki, Isamu
Abstract : The growth of dislocation-free and uniform GaN nanowires and high emission efficiency in a GaInN/GaN multi-quantum shell (MQS) are demonstrated. Simultaneous-supply-mode metal-organic vapor phase epitaxy and a high growth temperature are applied, and uniform GaN nanowires are obtained without a too high Si doping concentration. The GaInN/GaN MQS grown on the n-GaN nanowire has a thickness variation in the height direction, possibly owing to the interplane diffusion of Ga atoms. The MQS exhibits distributed CL emission in the case of a too high Si doping concentration in the n-GaN nanowires. For further improvement of the optical property in the MQS, a low-temperature-grown thin AlGaN shell, located just below the MQS active region, is introduced, and 6 times higher CL intensity is observed.